An empirical analysis of the determinants of borrowers’ default risk in peer-to-peer (P2P) lending in China - Huang, Xinyu (2019)
As a new model of Internet finance, P2P lending provides a new financing channel to the individuals and SMEs who are facing financing difficulties. P2P lending has become an important supplement to China’s traditional financial model. But with the rapid development of P2P lending, its hidden risks cannot be ignored, especially the borrower’s default risk. This problem not only causes the loss of capital to the lenders but also has a great negative impact on the reputation of P2P lending, which seriously hinders the further development of P2P lending. Therefore, the main objectives of this dissertation are to analyze the reasons for the borrower’s default risk, the influencing factors of borrower’s default risk, and how to prevent the default risk.